International regime building in Southeast Asia : ASEAN cooperation against the illicit trafficking and abuse of drugs - Emmers, Ralf (2009)
The Working Paper analyses whether an international regime against the illicit trafficking and abuse of drugs has been established in Southeast Asia. Its objective is to consider the circumstances that could have led to its formation as well as the conditions under which it may operate. The Working Paper claims that the existing cooperative structures for drug control in ASEAN present most of the characteristics of an international regime, though a relatively weak one. The cooperative process is based on a multilateral, long-term and normative dimension as well as on a convergence of views and interests on the need to tackle the illcit production, trafficking and abuse of drugs. The process has also been translated into an institutional structure. The Working Paper starts by reviewing how international regimes are discussed theoretically. It then discussed efforts made by ASEAN since 1972 to address the illicit trafficking and abuse of drugs problem. Adopting a neo-liberal institutionalist perspective, the final section examines the dynamics of the anti-drugs regime by analysing the existence of common interests, its institutional form, its geographical scope, its complementary approach to domestic efforts on drug control as well as its influence on states' behaviour.